2000
DOI: 10.1523/jneurosci.20-04-01386.2000
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-2 Mediates Neuronal Cell Death Induced by β-Amyloid

Abstract: beta-amyloid (Abeta) has been proposed to play a role in the pathogenesis of Alzheimer's disease (AD). Deposits of insoluble Abeta are found in the brains of patients with AD and are one of the pathological hallmarks of the disease. It has been proposed that Abeta induces death by oxidative stress, possibly through the generation of peroxynitrite from superoxide and nitric oxide. In our current study, treatment with nitric oxide generators protected against Abeta-induced death, whereas inhibition of nitric oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
280
1
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 335 publications
(300 citation statements)
references
References 46 publications
17
280
1
2
Order By: Relevance
“…5 (e12.5) and found that mutant embryos showed a proliferation index twice as high as wt littermates in the rostral part of the neural tube [74.973.9 and 37.273.6% (forebrain), 28.374.1% and 26.173.0% (hindbrain), respectively; see Figure 1a]. We then checked mutant embryos at a later stage (e13.5-e14) for expression of proneural markers such as nestin, delta1, notch1, or a later marker of nerve cells (class III b-tubulin).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 (e12.5) and found that mutant embryos showed a proliferation index twice as high as wt littermates in the rostral part of the neural tube [74.973.9 and 37.273.6% (forebrain), 28.374.1% and 26.173.0% (hindbrain), respectively; see Figure 1a]. We then checked mutant embryos at a later stage (e13.5-e14) for expression of proneural markers such as nestin, delta1, notch1, or a later marker of nerve cells (class III b-tubulin).…”
Section: Resultsmentioning
confidence: 99%
“…However, activation of Casp2 was undetectable in both ETNA cell clones. It should be mentioned that Abmediated death requires Casp2 in hippocampal neurons, sympathetic neurons and PC12 cells, 28 and requires Casp12 in primary cortical neurons. 29 This suggests that different pathways of death can be activated in different neuronal cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Aggregated, but not soluble forms of A␤ are highly neurotoxic (Estus et al, 1997;Ferreira et al, 1997;Troy et al, 2000). However, it has been reported that there does not seem to be a direct, simple correlation between levels of insoluble (i.e., aggregated) A␤ and cognitive deficits observed in transgenic mice that express a mutant form of human APP.…”
Section: Steroid Hormones and Neuronal Nachrsmentioning
confidence: 99%
“…Recent studies suggest that plaques, tangles, and caspase activation share a common pathway. A can activate caspases (Harada and Sugimoto, 1999;Ivins et al, 1999;Nakagawa et al, 2000;Troy et al, 2000;Yamakava et al, 2000). Activated caspases can, in turn, cleave tau, the main component of neurofibrillary tangles.…”
Section: Page 4 Of 31mentioning
confidence: 99%